Effect of docking on growth and carcass characteristics of Dubasi Desert sheep - El-Karim, A.I.A. (1980)
The growth of 30 docked and 30 intact male Sudan Desert lambs was studied to weaning. The mean birth weight, rate of gain to weaning and weaning weight of the docked group were found to be 3.9 kg, 119g/d and 18.5 kg respectively; those for the intact group were 4.1 kg, 116 g/d and 18.0 kg in the same order. The group difference regarding the three parameters was non-significant. The performance and carcass characteristics of 20 docked and 20 intact weaned lambs were studied under feedlot conditions. Daily rate of gain and feed conversion ratio were found to be 255 g and 6.46 for the the docking group and 238 g and 7.0 for the intact group, respectively. Carcass characteristics were not influenced by docking.